Genomic and fitness consequences of inbreeding in an endangered carnivore. Issue 12 (20th May 2021) - Hasselgren, Malin; Dussex, Nicolas; von Seth, Johanna; Angerbjörn, Anders; Olsen, Remi‐André; Dalén, Love; Norén, Karin
Abstract: Reduced fitness through genetic drift and inbreeding is a major threat to small and isolated populations. Although previous studies have generally used genetically verified pedigrees to document effects of inbreeding and gene flow, these often fail to capture the whole inbreeding history of the species. By assembling a draft arctic fox ( Vulpes lagopus ) genome and resequencing complete genomes of 23 additional foxes born before and after a well‐documented immigration event in Scandinavia, we here look into the genomic consequences of inbreeding and genetic rescue. We found a difference in genome‐wide diversity, with 18% higher heterozygosity and 81% lower FROH in immigrant F1 compared to native individuals. However, more distant descendants of immigrants (F2, F3) did not show the same pattern. We also found that foxes with lower inbreeding had higher probability to survive their first year of life. Our results demonstrate the important link between genetic variation and fitness as well as the transient nature of genetic rescue. Moreover, our results have implications in conservation biology as they demonstrate that inbreeding depression can effectively be detected in the wild by a genomic approach.